Writing for Distance Education. A Manual for Writers of Distance Teaching Texts and Independent Study Materials - International Extension Coll., Cambridge (England).; de Jardon, Linda King; International Extension Coll., Cambridge (England). (Washington, D.C. : Distributed by ERIC Clearinghouse, 1983)
Six instructional units offer guidance in the process of writing printed educational materials. Each unit provides objectives, writing exercises and activities, and end-of-unit discussion questions. Unit 1 considers the first steps in writing, emphasizing the importance of varying instruction according to student needs and background and discussing how people learn. Active learning and different types of learning activities are then examined in the second unit. The third addresses ways of improving a presentation, such as writing in an appropriate style; using clear, simple language; and trying alternative presentation forms, such as pictures and diagrams. Unit 4 covers all steps of production and starts students on an individual project to produce materials in their own subject. Four stages of systematic planning are covered: identifying a need, formulating objectives, listing resources and constraints, and preparing an outline plan. Unit 5 emphasizes specific instructional writing skills with advice on distinguishing between different kinds of instructional materials, what to include and how to organize it, and writing correspondence units. The final unit outlines processes of editing, piloting, reproducing materials, administration, tutoring, and evaluation. Four supplements provide additional information on learning theories, behavioral objectives, media, and readability and layout. (LMM)
Students.
Microfiche.
Keywords: Correspondence Schools; Design Requirements; Distance Education; Evaluation Methods; Instructional Development; Instructional Materials; Layout (Publications); Learning Processes; Material Development; Objectives; Writing Skills; Guides, Classroom -- Learner